ROLE OF ANTIOXIDANTS AND NUTRITION IN OXIDATIVE STRESS: A REVIEW - Kale, Mayura A.; Bindu, Suparna M.; Khadkikar, Pratima (International Journal of Applied Pharmaceutics, 2015)
Human body is known to experience positive stress that keeps it vigilant and protects it from biological and physical threats. This stress turns negative when a person is confronted with continuous challenges. Also, stress and nutrition have always run in synergism with each other. Nutritional value of a person's diet depends on the overall mixture or balance of food that is eaten over a period of time, as well as on the needs of the individual. The body relies on obtaining its anti-oxidants from food and other supplements. These nutritional requirements of antioxidants are enormously altered in diseased conditions. In view of the immense medicinal importance of antioxidants, an effort has been made in this article to bring together information about the role of nutrition and antioxidants such as carotenoids, vitamins, some important minerals in combating free radical generation and in general, boosting normal immune mechanisms. The present review is an attempt to generate interest in the scientific fraternity of their immense potential in preventing and treating several common diseases. Keywords: Antioxidants, Free radicals, Balanced diet, Nutrition, Oxidative stress, Vitamins.